Skrining dan Edukasi Anemia Pada Remaja Putri di Sekolah Menengah Pertama Muhammadiyah 1 Gamping - Yanita Trisetiyaningsih; Hutasoit , Masta; Yati, Dwi; Supadmi, Fransisca Romana Sri (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
Anemia is a condition in which the level of hemoglobin in the blood is less than normal. Adolescent girls are a group that is prone to anemia due to several factors including malnutrition, menstruation, socioeconomic status and adolescent knowledge. Providing education is one way to increase adolescent knowledge related to anemia in adolescents. This service activity will be carried out at SMP Muh. 1 Lime. This activity begins with the preparation stage, coordinates and prepares facilities and infrastructure, the implementation stage begins with the pretest and the provision of education using animated videos, as well as posttest. The final stage is reporting activities and follow-up plans. This activity is a follow-up to research that has been carried out in 2021 with the title "Increasing Adolescent Knowledge About Anemia Through Problem-Based Animation Education at SMP N.1 Kalasan". Based on the results of hemoglobin examination in 8th grade students, 18 people had hemoglobin levels below normal (<12g/dl). Of the 18 students who had anemia, there were 2 students who had severe anemia where Hb was 4.1g/dl and 8.5gr/dl. Based on the results of the pretest, it was found that the average knowledge of 8th grade students of Muhammadiyah 1 Gamping Junior High School was 78. This was because screening and education about anemia had never been carried out on adolescent girls at Muhammadiyah 1 Gamping Junior High School. The intervention provided in this activity is education about anemia in young women using animated media that has been used in the 2021 research. The results obtained after being given education, students were able to correctly answer some of the questions asked at the end of the activity. This proves that education using animation media can increase students' knowledge about anemia in adolescent girls.